1985
DOI: 10.1136/jcp.38.10.1158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an avidin-biotin immunoassay with three commercially available immunofluorescence kits for typing of herpes simplex virus.

Abstract: SUMMARY An avidin-biotin complex system was compared with three commercially available immunofluorescence kits for serotyping herpes simplex virus isolates from clinical specimens. Sensitivity values showed that the Electro-Nucleonics and Immulok reagents were useful in detecting the presence of virus, whereas the predictive values showed that the Syva and Immulok reagents possessed adequate discrimination between the herpes simplex virus serotypes. The avidin-biotin complex system was equal or superior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The blood samples utilized in this study were derived from patients diagnosed at metastatic stage of cancer (Supplementary Table 1) where distant metastases was detected (M1 Stage in TNM classification scheme) and could serve as a proxy tissue for practical purposes [46]. The high affinity of avidin for biotin [47] forms the fundamental basis of the biotin-avidin mediated EIA. Multiple HRP labeled avidin can bind to biotin labeled antibody, forming the biotin-avidin complex and thereby producing enhanced intensity of the immune reaction.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The blood samples utilized in this study were derived from patients diagnosed at metastatic stage of cancer (Supplementary Table 1) where distant metastases was detected (M1 Stage in TNM classification scheme) and could serve as a proxy tissue for practical purposes [46]. The high affinity of avidin for biotin [47] forms the fundamental basis of the biotin-avidin mediated EIA. Multiple HRP labeled avidin can bind to biotin labeled antibody, forming the biotin-avidin complex and thereby producing enhanced intensity of the immune reaction.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Direct identification of the virus can be done with cell culture, which is rather timeconsuming, electron microscopy, or antigen detection, quite often based on immunofluorescence techniques. [1][2][3][4][5][6][7] Reported sensitivities of different techniques vary widely. In addition, amplification of DNA from skin swabs by polymerase chain reaction (PCR) has also been established.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of cutaneous infections with herpes simplex virus (HSV) has proven difficult, as serum antibody tests sometimes are not suitable for that purpose. Direct identification of the virus can be done with cell culture, which is rather time‐consuming, electron microscopy, or antigen detection, quite often based on immunofluorescence techniques 1–7 . Reported sensitivities of different techniques vary widely.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the FA conjugates should be used to stain cells which have up to 2+ CPE; however, with HSV this may not always be possible. Barnard et al (1) also noted problems in staining clinical isolates with commercial reagents and believed this resulted from the very restrictive epitope range of the monoclonal antibody. In their study, most of the isolates which did not stain with Syva reagents were HSV-2, whereas in our study, all three isolates were identified as HSV-1 by another reference laboratory.…”
mentioning
confidence: 99%